(untitled) (Voice: A Biannual & Bilingual Journal, 2023)
Nepal and India have trade relations since pre historic age. The pattern of trade between these two countries has not remained same from prehistoric age to the current period. Nepal and British India signed first treaty of commerce in 1st March, 1792. Nepal’s had trade surplus with British India before both the countries signed a treaty of friendship on December 21, 1923 AD. Nepal’s trade deficit with India has been increasing. Nepal introduced country-wise and commodity-wise trade diversification initiatives to raise its export to India and lessen its reliance on India in international trade. Nepal has brought several reformations in trade policies though after 1991 when it liberalized its economy for increasing export and reducing volume of trade deficit. This study compares India-Nepal trade in past before down of democracy in Nepal, in between 1950 to 1990 and after 1990 in order to analyse effects of various trade treaties and policies in Nepal-India trade. It uses historical-analytical method using secondary sources of data to carry out the study. It covers data from 1900 AD to 2020/21. The study finds that various revisions in trade treaties between Nepal and India and trade reformation policies have not been effective in increasing export of Nepal, its trade deficit and dependency in India.